Nutrition Counseling Towards Maintaining an Ideal Body Weight for PKK Mothers of Claster Nirwana Arenjaya Residents - Fadhilah, Tri Marta; Putri, Nabilla Desica; Damayanti, Savira Salma; Arifah, Luthfiya Zahra (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2025)
A healthy and balanced diet is very important in preventing non-communicable diseases and maintaining ideal body weight. However, public awareness and understanding, especially adult women as the main determinant of family food consumption, are still limited. This study aims to determine the increase in knowledge of adult women and to determine the nutritional status of adult women in the Nirwana Aren Jaya Cluster. The method used is health education in the form of interactive lectures with poster and leaflet. To assess the increase in knowledge, a pre-test and post-test were conducted, as well as Body Mass Index (BMI) measurements to assess nutritional status. A total of 18 respondents participated in this activity in full. The results showed a statistically significant increase in knowledge, with an average pre-test score of 7.11 and a post-test of 8.5 (p-value = 0.019). BMI measurements showed that 55.6% of respondents were in the obese category, 22.2% were overweight, and 22.2% had normal nutritional status. This study proves that nutritional education delivered through simple visual media can effectively increase mothers' knowledge about the importance of consuming healthy foods. This can be an initial step in efforts to improve diet and reduce the risk of obesity in the community. Consistent and easily accessible education is needed to form long-term behavioral changes for improving quality of life. The conclusion of this activity is an increase in knowledge in adult women and knowing the nutritional status with a high obesity category in adult women.